Studi Kualitatif Dampak Penggunaan Gadget pada Perkembangan Anak Usia Balita 1-5 Tahun - Intan Nurhayati; Ria Andriani; Dhinny Novryanthi (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Background: The phenomenon of Gadget use among children under five is increasing and has become an inseparable part of everyday life. This raises concerns about the impact on child development. There is a risk that excessive use of Gadgets in children under five can disrupt various aspects of development, including physical, cognitive, social and emotional. Children who are too fixated on Gadgets tend to interact less with their surroundings, including with their parents and peers. This can affect their social skills in the future. Objective: The general objective of this research is to understand the impact of Gadget use on the social development of children under five. Method: This research method uses qualitative methods with interviews, observation and documentation, with 5 samples. Results: the use of Gadgets in early childhood in the Cikondang area, Citamiang District, has a significant impact on children's development, both positively and negatively. Suggestion : Efforts need to be made to limit the use of Gadgets and provide stricter supervision from parents and society as a whole to ensure children can develop optimally.